Necesidad de reformar el artículo 2232 del código civil del Ecuador en lo referente a la determinación del valor de la indemnización por daño moral - Albán Gaibor, Edgar Gerardo (2014)
Damage means any offense moral subjectively considered, an extra-patrimonial rights of the domestic law gives individuals and as objectively manifested an injury to the right holder or the victim of the offense, causing a detriment, impairment or violation of the economic rights. The damage can be assessed objectively moral in two ways as pecuniary and non-pecuniary, not admitting the first economic valuation but if affects the victim's assets such as when a writer is accused of copying his work to another writer, and while the second does not affect the property and is in pain, fear, humiliation and suffering experienced by the victim as a result of the unlawful activity of the offender. In our legal system both the first and the second giving rise to the obligation to repair them financially. This research was the result of enforcement, hearing problems always an issue as brought to light always being mentioned in the media to dictate failures with some sentences with huge amounts of compensation in some cases and in other only with symbolic values, totally divorced from social reality in the country. The Civil Code of Ecuador provides in Article 2232, third paragraph: "The compensation for moral damages may be sued if such damage is the proximate result of the wrongful act or omission of the defendant, being the law of the court to determine the value of compensation attentive circumstances envisaged in paragraph one of this article. " The foregoing statute has left a huge open field prudent interpretation of the judge, has generated both excesses victim who feels moral hazard, as the trial judge, processes and resolves the action raised, reaching values determined laughable in some cases or other huge fortunes. Given these facts, there is a need to recommend an alternative solution to the problem of formulating a reform of Article 2232 of the Civil Code of Ecuador in the third paragraph as regards the amount of compensation for moral damages.